Longitudinal associations between self-regulation and physical activity behavior following metabolic bariatric surgery; an exploratory study - Sundgot-Borgen, Christine; Baardstu, S.; Bond, D. S.; Sniehotta, Falko F.; Bergh, I.; Mala, T.; Rø, Ø; Kvalem, I. L. (International journal of behavioral nutrition and physical activity, 2025)
Low adherence to moderate-to-vigorous physical activity (MVPA) recommendations among patients undergoing metabolic bariatric surgery (MBS) is common. However, understanding of psychosocial factors that contribute to low adherence levels is limited. Self-regulation plays a key role in MVPA adherence. Still, the longitudinal and bidirectional associations between self-regulation and MVPA in the MBS patient population remains unexplored. This study aimed to investigate how self-regulatory processes of action- and coping planning, and action control, developed over a 1-5-year post-surgery period, and explore longitudinally the direct, indirect, and bidirectional associations between this development in self-regulation and MVPA assessed at 1- and 5-years after surgery. Participants from the Oslo Bariatric Surgery Study (OBSS) completed MVPA-specific self-regulation questionnaires at 1-, 3-, and 5-years post-surgery and wore ActiGraph monitors for seven days at 1- and 5-years to assess daily MVPA. Second-order latent growth curve modeling examined changes in the three self-regulation constructs, followed by path analysis to explore direct, indirect, and bidirectional associations between baseline levels and changes in self-regulation, and MVPA at 1- and 5-years post-surgery. A total of 205 (82.8%), 195 (64.6%), and 79 (26.2%) male and females (77%) participated at 1-, 3-, and 5-years after surgery, respectively. Action- and coping- planning decreased with.52 and.30 sd, respectively, over 1-5 years post-surgery. This indicates a moderate effect size. Action control remained relatively stable. Indirect and bidirectional path analyses showed that only higher levels of action control at 1-year were indirectly associated with higher MVPA at 5-years through their impact on MVPA at 1-year, whereas there were no indications of bidirectional associations from MVPA levels at 1-year to changes in any of the self-regulation constructs over time. After MBS, patients exhibited low self-regulation 1-year post-surgery, and many participants faced growing difficulties in self-regulating over time. Self-regulation at 1-year was positively linked to MVPA, with action control only, being associated with MVPA at 5-years. However, no bidirectional associations from MVPA to self-regulation were found. These findings suggest further research is needed to test interventions targeting action control to improve MVPA adherence and optimize surgical outcomes and overall health after MBS.
Gesehen am 30.06.2025